Exploring the effect of hole localization on the charge–phonon dynamics of hole doped delafossite. (10th August 2017) - Mazumder, Nilesh; Mandal, Prasanta; Roy, Rajarshi; Ghorai, Uttam Kumar; Saha, Subhajit; Chattopadhyay, Kalyan Kumar
Abstract: For weak or moderate doping, electrical measurement is not suitable for detecting changes in the charge localization inside a semiconductor. Here, to investigate the nature of charge–phonon coupling in the presence of gradually delocalized holes within a weak doping regime ( 10 16 cm −3 ), we examine the temperature dependent Raman spectra (303–817 K) of prototype hole doped delafossite C u C r 1 − x M g x O 2 − y S y ( x = 0/0.03, y = 0/0.01). For both E g and A 1 g phonons, negative lineshape asymmetry and relative thermal hardening are distinctly observed upon S O × and ( M g C r + S O × ) doping. Using Allen formalism, charge density of states at the Fermi level per spin and molecule, and charge delocalization associated to a − b plane, are estimated to increase appreciably upon codoping compared to the c -axis. We delineate the interdependence between charge–phonon coupling constant ( λ ) and anharmonic phonon lifetime ( τ a n h ), and deduce that excitation of delocalized holes weakly coupled with phonons of larger τ a n h is the governing feature of observed Fano asymmetry ( q ) reversal.